2017
DOI: 10.1016/j.avsg.2017.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome of Carotid Artery Stenting According to Provider Specialty and Volume

Abstract: Background Several studies have demonstrated better outcomes for carotid endarterectomy with high-volume hospitals and providers. However, only a few studies have reported on the impact of operator specialty/volume on the perioperative outcome of carotid artery stenting (CAS). This study will analyze the correlation of CAS outcomes and provider specialty and volume. Methods Prospectively collected data of CAS procedures done at our institution during a 10-year period were analyzed. Major adverse events (MAEs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Several prior studies have shown similar postoperative outcomes of CAS when performed by different specialities. [24][25][26][27][28] However, in a subgroup analysis of CREST, the periprocedural risk of stroke following CAS was higher when performed by vascular surgeons compared to interventional cardiologists and neuroradiologists. 29 We have previously reported short-term outcomes of CEA and CAS for high-grade carotid artery stenosis performed by a single vascular surgeon at our institution and showed similar outcomes between the 2 procedures that were also comparable to those of CREST.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Several prior studies have shown similar postoperative outcomes of CAS when performed by different specialities. [24][25][26][27][28] However, in a subgroup analysis of CREST, the periprocedural risk of stroke following CAS was higher when performed by vascular surgeons compared to interventional cardiologists and neuroradiologists. 29 We have previously reported short-term outcomes of CEA and CAS for high-grade carotid artery stenosis performed by a single vascular surgeon at our institution and showed similar outcomes between the 2 procedures that were also comparable to those of CREST.…”
Section: Discussionmentioning
confidence: 98%
“…28 Another study by AbuRahma et al on 30-day rates of MAEs after CAS performed by different specialties were 3.1% with interventional cardiology, 6.3% with vascular surgeons, 7.1% with interventional radiologists, and 6.7% with interventional vascular medicine. 24 However, in an analysis of the National Inpatient Sample NIS, Sgroi et al reported that the majority of CAS procedures in the country were performed by vascular surgeons and that postoperative unadjusted outcomes of stroke and MI were similar between the vascular surgeons and interventional specialties. 28 The authors concluded that the volume of cases performed by a provider, rather than the provider's specialty, seems a stronger predictor of adverse outcomes for CAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…577 Vogel et al 587 588 However, the study showed that the interventionalists did have increased hospital charges and length of stay compared with the surgeons. Recently, AbuRahma et al 589 reported on the clinical outcome of CAS according to provider specialty and volume. Four hundred fourteen CAS procedures (44% for symptomatic indications) were analyzed.…”
Section: Cas Provider Specialtymentioning
confidence: 99%
“…AbuRahma et al 56 ) analyzed the correlation of CAS outcomes with operator’s specialty and volume. In their study, they analyzed prospectively collected data from 414 CAS procedures performed at their institution over a 10-year period.…”
Section: Technical Predictors Of Perioperative Stroke/death After Casmentioning
confidence: 99%